2020
DOI: 10.1126/scitranslmed.aay1318
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes secreted by hiPSC-derived cardiac cells improve recovery from myocardial infarction in swine

Abstract: Cell therapy treatment of myocardial infarction (MI) is mediated, in part, by exosomes secreted from transplanted cells. Thus, we compared the efficacy of treatment with a mixture of cardiomyocytes (CMs; 10 million), endothelial cells (ECs; 5 million), and smooth muscle cells (SMCs; 5 million) derived from human induced pluripotent stem cells (hiPSCs), or with exosomes extracted from the three cell types, in pigs after MI. Female pigs received sham surgery; infarction without treatment (MI group); or infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 70 publications
1
113
0
3
Order By: Relevance
“…These cardioprotective effects were demonstrated to be associated with the delivery of protective miRNA such as Nanog-regulated miR-21 and hypoxia-inducible factor (HIF)-1α-regulated miR-210 to H9C2 cardiomyocytes in vitro. Gao et al [32] demonstrated that exosomes from human induced pluripotent stem cell-derived cardiomyocytes (iCM) also have cardioprotective effects in a swine MI model by the measurement of left ventricular ejection fraction, wall stress, myocardial bioenergetics and cardiac hypertrophy. These exosomes exhibited anti-apoptotic and angiogenic functions.…”
Section: Application Of Hipscs-derived Exosomes In Diseasesmentioning
confidence: 99%
“…These cardioprotective effects were demonstrated to be associated with the delivery of protective miRNA such as Nanog-regulated miR-21 and hypoxia-inducible factor (HIF)-1α-regulated miR-210 to H9C2 cardiomyocytes in vitro. Gao et al [32] demonstrated that exosomes from human induced pluripotent stem cell-derived cardiomyocytes (iCM) also have cardioprotective effects in a swine MI model by the measurement of left ventricular ejection fraction, wall stress, myocardial bioenergetics and cardiac hypertrophy. These exosomes exhibited anti-apoptotic and angiogenic functions.…”
Section: Application Of Hipscs-derived Exosomes In Diseasesmentioning
confidence: 99%
“…These data collectively suggest an alternative mechanism of action, based on paracrine signaling, where cell secreted signals, including extracellular vesicles, mediate cardiac repair via increasing CM survival and neovascularization and decreasing apoptosis and inflammation (206). Paracrine signaling was further evidenced by a study where exosomes secreted from combination of iPSC-derived CMs, ECs, and SMCs yielded cardioprotective effects similar to that obtained from direct cells injection in a porcine model of MI (195). Further, acellular hCMPs composed of non-viable/irradiated cells (39) or decellularized porcine myocardial tissues (139) have shown therapeutic benefits after transplantation, through the proposed mechanism of mechanical stabilization.…”
Section: Mechanisms Of Action Of Hcmpsmentioning
confidence: 84%
“…Long-term imaging of the patch was not reported. Pre-clinical research from Menasche's lab suggests that many if not all the benefits of this approach might be due to paracrine effects [156].…”
Section: Mixed Products and Bioengineered Constructsmentioning
confidence: 99%
“…Advances are being made in adequate cell isolation; expansion and growth of patches large enough for large animal testing and eventual human use; and adequate maturation of cardiomyocytes into structures that mirror those in native myocardium both structurally and functionally, including excitability and contractility, action potential conduction, calcium handling, and proper cardiomyocyte size and function [154,[157][158][159]. As with many of the findings in the field of cell therapy, much of the improvement observed in several of these studies is felt to be due to cell secretomes, and not a direct action of the cells themselves [156]. An interesting approach to a cell-free patch approach has recently been reported, suggesting that even cellular bioengineering approaches may find clinical application through a cell-free route [160].…”
Section: Mixed Products and Bioengineered Constructsmentioning
confidence: 99%